Synthesis, Characterization and Anti-Corrosion Properties of Novel Quinolinol on C-steel in a Molar Hydrochloric Acid Solution - Galai,M (2017)
New quinoline, namely 5-(ethoxymethyl)-8-quinolinol (M-QN), has been synthesized and characterized by different spectral methods, such as 1H NMR, 13C NMR and IR spectra. Its inhibitive action against the corrosion of carbon steel in 1.0 M hydrochloric acid solution was investigated at different temperatures in the range from 25±2 to 55±2 °C by a series of known techniques, such as weight loss, open circuit potential (OCP), electrochemical impedance spectroscopy (EIS) and Tafel polarization measurements. The inhibition efficiencies obtained from all employed methods are in good agreement with each other. The obtained results show that M-QN compound is a very good inhibitor with an efficiency of 97.7 % at 10-3 M additive concentration in a 1.0 M HCl solution. The inhibition efficiency increased with an increase of the inhibitor's concentration. Changes in impedance parameters (Rct and Cdl) were indicative of adsorption of the compound (M-QN) on the metal surface, leading to the formation of a protective film. Tafel polarization measurements showed that M-QN inhibitor is of a mixed type. The adsorption of the inhibitor on the surface of carbon steel in a 1.0 M HCl solution was found to obey Langmuir's adsorption isotherm. The kinetic and thermodynamic parameters for carbon steel corrosion and inhibitor adsorption, respectively, were determined and discussed. On the bases of thermodynamic adsorption parameters, comprehensive adsorption (physisorption and chemisorption) for the studied inhibitors on carbon steel surface was suggested.